The requirements of forestry cooperative organization development in China: a case study of different stakeholder groups - Wu Jing; Han Feng; Gao Yang; Wen Yali (Metsanduslikud Uurimused, 2013)
After China’s collective forest tenure reform, cooperation organization has played an important role on the development of community forestry. In order to analyse the different stakeholders’ opinion and suggestion on the development of forestry cooperation organization, publicizing and training, participatory interview, brainstorming, and questionnaire surveys were used in this case study. According to the results it can be seen that the real motivation for the development of cooperatives is farmers’ demands and the demands come from farmers’ pursuit of interests in forest industry. Cooperatives in China are still in the early stage of development, and the cooperative laws cannot cover all the basic features of the forestry and the cooperatives. Therefore, the relevant laws and guarantee systems for resource exploitation and management, publicity and demonstration, forestry technology training as well as the preferential policies such as tax breaks, are needed for the sound development of China’s forestry cooperation organization.